Ketidakstabilan Aliran Sekunder pada Saluran Lengkung Berpenampang Persegi - Nursubyakto . (Jurnal Teknik Mesin (Sinta 3), 2010)
Secondary flow is the counter rotating vortex that appears in the channel when a fluid flows in a curved channel. The occurence of this secondary flow is caused by imbalance between centrifugal force and pressure on the outer wall of the channel. When Dean number is increased the additional secondary flow appears to the main secondary flow and/or disappears. This paper investigated the occurence of the additional secondary flow to the main flow with rectangular cross section and the radius of curvature varied from 1 to 10. The result shows that increament of curvature ratio the additional Dean voritces appears and beyond of ratio of 4 is constant. The effect of the additional secondary flow to the friction factor is also predicted.